Índice del segundo molar (I2M) de Cameriere, para estimar la edad dental en individuos colombianos. (2021)
The objective of this study was to verify the cut-off points of the Cameriere 2nd molar index for estimating dental age in a sample of 96 panoramic radiographs of Colombian individuals, 49 males and 47 females between the ages of 12 and 17 years.